Evaluating Importation of Aquatic Ornamental Species for Biosecurity Purposes - Atalah, Javier; Davidson, Ian C.; Thoene, Maike; Georgiades, Eugene; Hutson, Kate S. (Frontiers in Ecology and Evolution, 2022)
The aquatic ornamental species (AOS) trade is a significant pathway for the introduction and establishment of non-indigenous species into aquatic environments. The likelihood of such occurrences is expected to increase worldwide as industry growth continues and warmer conditions emerge under future climate scenarios. This study used recent (2015 – 2019) New Zealand importations data to determine the composition, diversity, abundance, and arrival frequency of AOS. Our analysis revealed that ca. 300,000 aquatic ornamental individuals are imported annually to New Zealand, with freshwater fish comprising 98% of import quantities. Despite the relatively small market size, the estimated AOS diversity of 865 taxa (89% and 9.5% identified to species and genus level, respectively) is comparable to larger markets with ~60% of taxa being of marine origin. Species (n = 20) for further investigation were prioritised based on quantity and frequency of import. These prioritised AOS were exclusively tropical and subtropical freshwater fish and align with the most frequently imported AOS globally, including the top three: neon tetra (Paracheirodon innesi), guppy (Poecilia reticulata), and tiger barb (Puntigrus tetrazona). Species distribution modelling of the 20 prioritised AOS predicted that 13 species are suitable for New Zealand’s current climate conditions, most notably sucker-belly loach (Pseudogastromyzon myersi), white cloud mountain minnow (Tanichthys albonubes), and golden otocinclus (Macrotocinclus affinis). Potential changes in habitat suitability were predicted under future climate scenarios, with largest increases (29%) for Po. reticulata. The described approach provides an adaptable framework to assess establishment likelihood of imported AOS to inform regulatory decision making.